A case report on broad ligament fibroid mistaken as pregnancy - Dulewad, Shirish; Chandak, Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Leiomyoma is the commonest benign uterine condition arising from smooth muscles. Extra uterine leiomyoma is rare. The incidence of broad ligament fibroid is less than 1%. Because of its rarity broad ligament fibroid poses specific diagnostic difficulties causing an error in making the final diagnosis and therefore the management. Here we report a case of rare broad ligament fibroid got neglected sadly in this modern era, where the facilities like USG which can easily diagnose this rare entity are readily available. Presented as ANC with no labor pains and accidentally diagnosed as a case of huge broad ligament fibroid. Managed surgically by myomectomy with conservation of uterus and bilateral internal iliac artery ligation for minimizing bleeding.